Karakter dan Proses Pembentukan Rangkaian Fasies Endapan Kuarter di Paparan Danau Maninjau, Kabupaten Agam (Sumatera Barat) - Herman Moechtar (Pusat Survei Geologi, 2006)
The Quatenary sediments in the studied area can be divided into fraction of coarse-grained sediments, fine-grained sediments, and both mixed grained sediment. They consist of: (a) floodplan facies, (b) floodplain facies which are influenced by lake level rising or falling, (C) fluvial channel facies and (e) lake facies.The Quaternary sediments on margin lake Maninjau is the sedimentological response to allogenic mechanism controls. The allogenic controls are the climate, tectonics and lake level. The climate determines water and sediment as wells as the type of intervaI stratigraphic changes that can be recontructed. Tectonic and lake leveI set boundary condition to the energy of sediment supply also occurred. Keywords: fasies, depositional environment, forming control factor